Effects of Scutellaria baicalensis Extract on Gout-Induced Rats - Eunchang Lee; Ho-Sueb Song (Journal of Acupuncture Research, 2023)
Background: This study aimed to investigate hyperuricemia, renal inflammation, and xanthine oxidase (XO) activity improvement in a rat model treated with Scutellaria baicalensis extract (SBE). Methods: The rats were divided into 4 groups (n = 5 each), including sham, potassium oxonate (PO) injected hyperuricemia (control group), PO + 10 mg/kg allopurinol administrated (allopurinol group), and a PO + 50 mg/kg SBE administrated (SBE group), to investigate the effectiveness and molecular mechanisms of SBE. The effects of SBE on PO-induced hyperuricemia rats, renal inflammation, and XO activity were measured. Body weight and organ index of the kidney and liver were measured in PO-induced hyperuricemia rats, and serum uric acid level was extracted from whole blood and was measured. Renal inflammation was observed under a microscope after sections. XO activity was measured by liver tissue and serum XO levels. Results: Organ indexes of the kidney and liver in rats were significantly decreased in the allopurinol group than in the control group and with no significant difference in the SBE group. A PO injection for 5 days significantly increased serum uric acid levels in the control group compared to the sham group. Meanwhile, the SBE and allopurinol groups have significantly decreased serum uric acid levels compared to the control group. The SBE group revealed effectively improved renal histopathological changes compared to the control group. The XO inhibitor, allopurinol, significantly decreased XO activity. Additionally, SBE significantly lowered XO activity in rats. Conclusion: SBE can be used as an effective treatment for gout in the future.